Sustainability of Rubber Farmers Cooperatives: Empirical Evaluation of Determining Factors - Kajohnjak Nuanphromsakul; Katarzyna Szczepańska‐Woszczyna; Sebastian Kot; Singha Chaveesuk; Wornchanok Chaiyasoonthorn (Agris on-line Papers in Economics and Informatics, 2022)
The study investigated the factors that influence rubber farmers' cooperatives from the perspective of sustainability in Thailand. The research adopted a quantitative survey methodology with data purposively collected from 434 Thai rubber farmer groups. The variables included trust, sustainability, perceived value, satisfaction, loyalty, and brand image. The model was evaluated using Confirmatory Factor Analysis (CFA), while Structural Equation Modeling (SEM) was used to assess the hypotheses. The results indicated that the sustainability of the rubber farmers' cooperatives as a corporate entity is influenced by brand image, loyalty, and satisfaction. Trust was also found to have a significant effect on the satisfaction and loyalty of the rubber farmers' cooperatives. The research recommended that to enhance the sustainability of the rubber farmers' cooperative's brand image, loyalty, and satisfaction should be improved. The research's drawback is that it only looked at the rubber farmer cooperatives of Thailand as a corporation, and therefore, these factors should be taken into account when applying these results outside of this scope.
Keywords: Cooperative Studies and Economics